Cavernous cervical hemangioma: An incidental finding - Shopov, Spasimir Todorov (Indian Journal of Case Reports, 2020)
Cavernous hemangiomas of the uterine cervix are very rare benign tumors. They are usually more common around the third decade, but around the fifth decade, their frequency is even rarer. Sometimes, they can cause obstetric and gynecological complications, but most are asymptomatic and are detected by chance. Surgical treatment is usually the means of choice, which, in most cases, is performed in connection with other pathologies. We present a case of cervical hemangioma in a 58-year-old woman who was diagnosed accidentally. The reason for consulting a gynecologist was the weak postmenopausal bleeding for 6 months. Ultrasonographically, intramural leiomyoma of the uterine corpus was detected. Atrophic endometrium was found from the test abrasion. A total hysterectomy with salpingo-oophorectomy was performed. The histological examination confirmed the diagnosis: Cavernous hemangioma of the cervix. This case supports the fact that postmenopausal bleeding may also be due to cavernous hemangioma of the cervix.